Pengembangan Industri Rumah Tangga Minuman Segar “Mba Ren” di RT 40 Kelurahan Sungai Nangka, Balikpapan - Sinaga, Ovigeria Subroto; Pathul Pauji; Intan Sabila; Rizki Indriani; Mersiana (Scimadly Publishing, 2023)
Fresh drinks in the form of herbal medicine are one type of drink that is popular with Indonesian people. Apart from its relatively cheap price, herbal medicine is also considered to provide health benefits. Many Indonesian people like to consume herbal drinks, which in turn opens up opportunities for businesses to make them. Forms of herbal medicine production businesses are generally still small in size or what we often refer to as Small, Micro and Medium Enterprises or MSMEs. Management by the community in the form of small businesses is generally still carried out simply, both in production activities and financial administration management. One of the innovation development activities carried out by STIE Madani Balikpapan students and lecturers is providing assistance to improve management of both production and financial administration in these small businesses. Several mentoring and innovation development activities that have been carried out at the